Study of thyroid hormones free triiodothyronine (FT3), free thyroxine (FT4) and thyroid stimulating hormone (TSH) in subjects with dental fluorosis - Hosur, Mahadevi B; Puranik, S R; Vanaki, Shrinivas; Puranik, Surekha R (European Journal of Dentistry, 2012)
Objective: Apart from its well-known deleterious dental and skeletal effects, fluoride excess can have toxic effects on many other tissues. Fluoride, when in excess, is known to interfere with thyroid gland function. Fluoride-induced thyroid disturbances similar to those observed in iodine deficiency state in spite of adequate iodine intake have been documented. Similar thyroid disturbances in individuals with dental fluorosis have not been well studied in populations with endemic fluorosis. This work was undertaken to study the effects of fluoride-induced thyroid disturbances in individuals with dental fluorosis.Methods: The study group included 65 subjects with dental fluorosis from endemic fluorosis populations. An additional control group was comprised of 10 subjects without dental fluorosis. The drinking water fluoride levels of the study populations were analyzed. Serum free FT3, FT4, and TSH levels of both groups were assessed.Results: All subjects with dental fluorosis had serum levels of thyroid hormones (FT3, FT4, and TSH) within the normal range, with the exception of 1 individual, who had elevated levels of TSH. Statistical significance was found when FT3 and TSH values were compared with different Dean’s index groups by a 1-way ANOVA test: FT3 (F = 3.4572; P=.0377) and TSH (F = 3.2649 and P=.0449).Conclusions: Findings of this study did not show any significant alterations in the levels of the thyroid hormones FT3, FT4, and TSH in subjects with dental fluorosis. Our observations suggest that thyroid hormone levels were not altered in subjects with dental fluorosis. Hence, future studies of this kind, along with more detailed investigations are needed. (Eur J Dent 2012;6:184-190)
Keywords: Dental fluorosis; fluorosis and thyroid hormones; fluoride and thyroid